New concept for molecular design of N-substituted 2-pyrrolidone derivatives towards advanced reprocessing method for spent ThO2 fuels. (December 2017) - Takao, Koichiro; Ikeda, Yasuhisa; Kazama, Hiroyuki
Abstract: A thorium oxide nuclear fuel cycle should be one of the promising options in the current U-Pu cycle conducted in most countries utilizing the nuclear energy. To make this fuel cycle more reasonable, it is still necessary to innovate the reprocessing method of the spent ThO2 fuels. In accordance with our former development of a selective precipitation method for the spent UO2 fuel reprocessing, its basic technology can also be applied to the spent ThO2 fuel reprocessing. Prior to the molecular design of N -substituted 2-pyrrolidone precipitants (NRPs), differences in the conditions of these spent fuel reprocessing processes especially for the concentrations of U(VI) and other relevant species were indicated. On this context, the demands in the spent ThO2 fuel reprocessing and requirements for the U(VI)-selective precipitant were summarized. Consequently, a confliction between the requirements arising from the fundamental conditions in the spent ThO2 fuel reprocessing has appeared. To overcome this situation, a structural motif of a double-headed NRP (DHNRP) was proposed as a new concept for molecular design of NRPs expected to be employed in the spent ThO2 fuel reprocessing. Accessibility of DHNRPs was successfully demonstrated by preparation of several compounds which follow this molecular design concept.